Exploring family perceptions and roles in pulmonary tuberculosis care: A phenomenological study in East Kolaka Regency - Setriawati, Yayudia; Al-Maidin, Achmad R. Muttaqien; Arwan, Yayudia Setriawati M.; Alim, Andi; Asnidar, Asnidar (Universitas Islam Negeri Alauddin Makassar, 2025)
Several studies conducted on tuberculosis (TB) management have largely focused on patient-centered interventions, with limited qualitative exploration of family perceptions and caregiving roles, particularly in rural Indonesian contexts. This study addresses that gap by examining how families perceive and engage in the care of pulmonary TB patients in the service area of UPTD Puskesmas Mowewe, East Kolaka Regency, in 2024. Employing a qualitative descriptive design with a phenomenological approach, data were collected through in-depth interviews, observations, and document reviews involving six informants, including family members of TB patients. The study reveals a spectrum of family perceptions, from comprehensive understanding to persistent stigma and misconceptions about TB transmission and treatment. These perceptions significantly influence caregiving behaviors, with some families offering strong emotional and logistical support, while others demonstrate limited involvement due to lack of knowledge and access to health information. Findings highlight that the family's role is central in supporting treatment adherence, facilitating access to healthcare, and promoting healthy practices within the household. The study underscores the need for structured education and empowerment programs tailored to families, especially in rural settings. These efforts are critical for enhancing family participation in TB care and achieving better public health outcomes. Recommendations include integrating family-based strategies into TB control programs and strengthening collaboration between healthcare providers and families.